2022
DOI: 10.33736/jcshd.4745.2022
|View full text |Cite
|
Sign up to set email alerts
|

Psychoeducation and Family Intervention by Parents of Children with Attention Deficit Hyperactive Disorder: A Comprehensive Review

Abstract: Attention Deficiency Hyperactive Disorder (ADHD) is a neurodevelopmental disorder that encompasses attention deficit and/or hyperactivity-impulsive issues. Parents, teachers, and caregivers are responsible for identifying children with ADHD by observing their social and emotional behaviour, examining their retention ability, and identifying their learning problems to provide the necessary remediation. This comprehensive review of over 54 articles examining the effectiveness of psychoeducation and suitable home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Parental involvement is seen as an important aspect in the learning development of ASD children. Previous research has demonstrated that parents' involvement in their ASD children's development can aid these exceptional children with delayed linguistic abilities (Yan et al, 2022), distracted or hyperactive behavior (Sin & Cheng, 2022), seizure or epilepsy disorder (Fombonne et al, 2022), deferred motor skills (Gajic et al, 2021), odd dietary and sleeping patterns (Bullivant & Woods, 2020), atypical emotional or mental states (Tajik-Parvinchi et al, 2020) and also delayed cognitive or educational abilities (Fenning & Butter, 2019). This article will examine the benefits of parental involvement in using AI techno-logies that affect autistic children's engagement with types of AI such as speech recognition software, intelligent tutoring system, machine learning, and also virtual learning application.…”
mentioning
confidence: 99%
“…Parental involvement is seen as an important aspect in the learning development of ASD children. Previous research has demonstrated that parents' involvement in their ASD children's development can aid these exceptional children with delayed linguistic abilities (Yan et al, 2022), distracted or hyperactive behavior (Sin & Cheng, 2022), seizure or epilepsy disorder (Fombonne et al, 2022), deferred motor skills (Gajic et al, 2021), odd dietary and sleeping patterns (Bullivant & Woods, 2020), atypical emotional or mental states (Tajik-Parvinchi et al, 2020) and also delayed cognitive or educational abilities (Fenning & Butter, 2019). This article will examine the benefits of parental involvement in using AI techno-logies that affect autistic children's engagement with types of AI such as speech recognition software, intelligent tutoring system, machine learning, and also virtual learning application.…”
mentioning
confidence: 99%